Investigation of surface roughness in machining oil palm wood - Harizam, M.Z.; Nukman, Y.; Anis, M.; Tamrin, K.F. (2012)
Oil palm industry is one of the largest agricultural plantation sectors in Malaysia. The total area under oil palm cultivation is over 2.65 million hectares, producing over 8 million tons of oil annually. The oil palm trunk is converted to oil palm wood after the replantation take place. The machining of wood process by cutting is a demanding technological process because of its specific structure. In many industries, accuracy and precision are crucial parameters for their production to achieve the best quality of cut. One of the qualities to be monitored is the surface roughness, Ra value which has direct implication on cut quality. Hence, this study was embarked to quantify the surface roughness of machining of oil palm wood. Three types of machining oil palm wood processes were conducted by using CO2 laser cutting, CNC milling and vertical saw machine. As a result, CO2 laser cut produced the best cut quality in comparison to other competing machining processes.